Natural Disaster Mitigation Through The Disaster Safe Education Unit (SPAB) Program After The Flash Flood Disaster In Batu City - Adi Yusuf Salsabilah; Syamsul Arifin; Djalaludin Djalaludin (Universitas Negeri Padang, 2022)
The Malang region, including the city of Batu, is arguably the city of education. Batu City in particular has a natural geographical condition that is still beautiful, but is also one of the areas prone to natural disasters. Exactly in 2021 the city of Batu was hit by flash floods that have killed victims and destroyed houses, damaged public facilities including the impact on learning in schools. With this incident, efforts are needed to educate the community, especially school residents, both educators and students regarding disaster mitigation in schools. The implementation of the Disaster Safe Education School (SPAB) program in schools must always be actively enforced. Through SPAB, all school residents will have a better understanding and know how to safeguard in the event of a natural disaster. The research method used is a qualitative method with a descriptive approach. The results showed that in the implementation of the Disaster Safe Education School Program (SPAB) in several schools affected by the